Power quality and neutral currents in three-phase power systems - Gursoy, E.; Gul, O.; Kaypmaz, A. (IEEE, 2003)
Nonlinear loads cause power quality problems, especially harmonic problems in buildings. To take into consideration these harmonic sources and effects some measurements are taken in a commercial building and in some of the nonlinear loads used in the building. The neutral current problem in three phase four-wire systems is searched in a model system for two cases of nonlinear load currents and neutral conductor. Harmonic effects to devices and neutral current related problems are given. Solutions to these problems are searched using measured values.